Pengaruh Penggunaan Mulsa Dan Pengolahan Tanah Terhadap Aliran Permukaan, Erosi Dan Selektivitas Erosi Pada Latosol Coklat Kemerahan Darmaga - Naik Sinukaban; . Sudarmo; Kukuh Murtilaksono (Jurnal Ilmu Pertanian Indonesia, 1991)
The purpose of this study is to evaluate the effects of conservation and straw mulch applications on runoff, erosion, selectivity in a cropping pattern of groundnuts - filed corn. Tillage systems used were zero tillage and minimum tillage, while straw mulch application used were 0, 30, 60, and 90 percent coverage on Reddish Brown Latosol, Darmaga. This study was carried out in the planting season of 1088/1989 (November 1988 to 1989). Groundnuts (Pelanduk variety) was planted immediately after land preparation, just before the straw mulches were applied. Field corn (Arjuna variety) was planted right after the harvesting of groundnuts. Runoff and soil loss were recorded and some samples were collected for laboratory analysis. The data analysis shows that runoff were significantly decreased by the minimum tillage system and soil loss were significantly decreased by the increasing straw mulch application with a linier relationship. Straw mulch coverage of at least 60 percent reduced the soil loss by more than 50 percent. However, the increasing straw mulch applications were not significantly effective to reduce plant nutrient loss. This is due to the increasing selectivity of erosion process by the increasing straw mulch application.